IoT BASED MEDICINE IN-TAKE SCHEDULER, REMINDER AND MONITORING SYSTEM - M.Nisha; S.Nivedhidha; D.Prabakaran (International Journal of Psychosocial Rehabilitation, 2020)
The IoT is an emerging technology that is being developed in many platforms. All the fields were implementing IoT to make their work easier and connecting this from the long distance by using the internet technology. Using this technology in the medical field can also create a good impact towards the developments in this field. A modern IoT based medicine box which will be used to schedule the medicine and also reminds and monitors the medical data is proposed here. This is made to be operated using the IoT technology and the medicine box has been controlled by arduino Node MCU microcontroller. It will also notify via message to the respective person.